Capturing structural changes of the S1 to S2 transition of photosystem II using time-resolved serial femtosecond crystallography. (2021) - Li, Hongjie; Nakajima, Yoshiki; Nomura, Takashi; Sugahara, Michihiro; Yonekura, Shinichiro; Chan, Siu Kit; Nakane, Takanori; Yamane, Takahiro; Umena, Yasufumi; Suzuki, Mamoru; Masuda, Tetsuya; Motomura, Taiki; et al.
No abstract available